Sistem Pendukung Keputusan Penilaian Kinerja Guru Menggunakan Metode Profile Matching - Suyanti Suyanti; Siska Nurul Marwiyah; Chandy Ophelia S (STMIK Budi Darma, 2022)
SMA Negeri 4 Sarolangun is a public school located in Mandiangin, Sarolangun Regency. As an educational institution, the role of the teacher is so important in transforming educational inputs. Therefore, to ensure the quality of teachers in teaching and learning activities (KBM) at school, SMA Negeri 4 Sarolangun conducts teacher performance assessments. Teacher performance appraisal is useful to motivate teachers to continue to improve their quality. In selecting the best teachers, the principal and staff experienced difficulties because they were assessed conventionally by assessing one that was included in the form of an assessment. In order for the selection to truly reflect and reduce subjectivity and to produce fast and precise information, a Decision Support System application for Scholarship Admissions is needed which is built using the Profile Matching method, using the Visual Basic.Net 2008 programming language and database using Microsoft Access 2007. The design The system was created using object-oriented modeling tools, namely Use Cases, Activity Diagrams, and Class Diagrams. With the construction of this new system, it is hoped that it can help the performance of the Student Affairs Section while speeding up the process of evaluating teacher work at SMA Negeri 4 Sarolangun